Percepções docentes a respeito da neuroeducação em um curso de medicina brasileiro: um estudo sequencial quanti-quali - Martins, Guilherme Henrique (2022)
Introduction: Starting from the technological advances of the biomedical sciences, educational research saw the emergence of a new area of interest: neuroeducation. Aiming to understand how the brain learns in a morphofunctional instance and apply it to education, this area has been gaining ground and is the subject of this dissertation. Objective: To evaluate the perception of professors of the medical course at the Belo Horizonte campus of the José do Rosário Vellano University regarding the principles of neurosciences applied to education. Materials and methods: Exploratory research were used with a mixed approach, in the quanti- quali sequential model, with execution in a virtual mode using the World Wide Web. The quantitative stage took place with the application of a questionnaire on neuromyths (n = 73) and the qualitative one was mediated by discussions of the principles of neuroeducation, using the focus group technique (n = 22). Descriptive statistics were used through measures of central tendency and dispersion and the data were presented through tables. Inferential statistical analysis was performed using Bonferroni's and Pearson's Chi-square tests, in order to assess the outcome variable and exposure variables. To establish the sequential process between the qualitative and quantitative stages, Cluster Analysis was carried. To analyze the discourse of the second stage of the research, the technique of Content Analysis was used. Results: The overall performance in the questionnaire was more than two thirds of correct answers. There was no statistical correlation between performance and sociodemographic data, but participants in the first stage of the research could be grouped into two clusters that were statistically similar to each other based on their perception of neuromyths. The expression of the participant’s speeches of the focus groups could be grouped in six analytical categories: impressions about the previously answered questionnaire, knowledge about the principles of neuroeducation, knowledge about the biological mechanisms of learning, perception about the relationship between emotion, memory and learning, role of meaningful learning and use of the senses in learning. Conclusion: The findings suggest that professors have knowledge about the structure and functioning of the brain, however, they rarely apply these understandings about educational processes.